AB0767 Cerebral Hemodynamics in Patients with Ankylosing Spondylitis. (9th June 2015) - Uygar, U.; Yildirim-Cetin, G.; Atilla, N.; Gişi, K.; Gokce, M.
Abstract : Objectives: It is known that there is a relationship between systemic inflammation and atherosclerosis. Atherosclerosis is one of the best known causes of cerebrovascular diseases. The aim of this study was to assess the cerebral blood flow velocity with using transcranial Doppler (TCD) ultrasonography in patients with ankylosing spondylitis (AS). Methods: A total of 30 patients aged 20 to 50-year-old with AS were enrolled in the AS group consecutively. Control group (non-AS group) consisted of 30 age and sex-matched, randomly sampled patients without AS such as fibromyalgia and had no possible risk factors for atherosclerosis. Bilateral middle cerebral artery (MCA) peak-systolic, end-diastolic, and mean blood flow velocities, Gosling's pulsatility index values, and Pourcelot's resistance index values were recorded with TCD by a neurosonologist blinded to AS and control groups. Results: In this study 30 participants in AS group (male/female: 4/26, mean age: 34, 7±5, 9) and 30 participants in control group (male/female: 4/26, mean age: 32, 3±4, 7) were evaluated. C-reactive protein (CRP) levels and cerebral blood flow velocities of bilateral MCA were significantly higher in AS group than the control group. This study highlights the persistent clinical and subclinical inflammation regarding atherosclerosis in patients with AS causes increased cerebral blood flow velocities. Our findings provide an insight to this association of AS and neurological manifestations. Conclusions: This study highlights the persistent clinical and subclinical inflammation regarding atherosclerosis in patients with AS causes increased cerebral blood flow velocities. Our findings provide an insight to this association of AS and neurological manifestations. Disclosure of Interest: None declared